2015
DOI: 10.1007/s11356-014-4053-7
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of pentachlorophenol by visible light Ν–F–TiO2 in the presence of oxalate ions: optimization, modeling, and scavenging studies

Abstract: The efficiency of heterogeneous photocatalysis using N-F-TiO2 as photocatalyst to degrade a priority pollutant, pentachlorophenol (PCP), in the presence of oxalates (OA) was investigated in detail. Response surface methodology was used to optimize the effect of three variables (catalyst concentration, OA/PCP ratio, and pH) on the photocatalytic degradation of pentachlorophenol. A quadratic model was established as a functional relationship between three independent variables and the degradation efficiency of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
(79 reference statements)
2
9
0
Order By: Relevance
“…The adequacy of the model was tested by the analysis of variance (ANOVA) and all the assumptions were analyzed for the meaningful results. Further violation of regression assumption was checked by several diagnostic methods, which included a graphical illustration of predicted vs. experimental values, to check the normality of the residuals by a normal probability plot of the studentized residuals, to look continually for errors made by studentized residuals vs. predicted plot, to check the outlier by cook distance, and the need of power transformations were checked by the Box-Cox plot [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…The adequacy of the model was tested by the analysis of variance (ANOVA) and all the assumptions were analyzed for the meaningful results. Further violation of regression assumption was checked by several diagnostic methods, which included a graphical illustration of predicted vs. experimental values, to check the normality of the residuals by a normal probability plot of the studentized residuals, to look continually for errors made by studentized residuals vs. predicted plot, to check the outlier by cook distance, and the need of power transformations were checked by the Box-Cox plot [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Since Minero et al [13] found in 2000 that the modification of F − could effectively improve the photocatalytic degradation activity of TiO 2 on phenol, fluorine modified TiO 2 has become a research hotspot [14][15][16]. Yu et al [17] showed that the crystallinity of anatase was improved after F − doping and F − could not only inhibit the formation of slate phase but also prevent anatase phase from transforming into rutile.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced oxidation processes (AOPs) such as ozonation, , Fenton, , H 2 O 2 /UV, , sonolysis, and photocatalysis have been widely and extensively explored to degrade environmental contaminants such as pentachlorophenol (PCP). Heterogeneous photocatalysis by TiO 2 is of considerable interest in AOPs due to its low toxicity and strong oxidizing power, which has been widely concerned as one of the most efficient methods to eliminate chlorophenols from water. , However, many reports focused solely on the degradation efficiency and remove conditions of the target compound. It should be worth noting that even after complete removal of PCP, acute toxicity was still observed, ,,,, which might be caused by the generation of toxic PCP byproducts including polychlorinated dibenzodioxins/furans, , tetrachloro-1,4-benzoquinone (TCBQ), ,, or other toxic intermediates. Therefore, determination of the only pristine PCP concentration may not be sufficient for evaluating an overall efficiency of wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%